2021
DOI: 10.1002/anbr.202000078
|View full text |Cite
|
Sign up to set email alerts
|

Cargo‐Templated Crosslinked Polymer Nanocapsules and Their Biomedical Applications

Abstract: Cargo‐templated crosslinked polymer nanocapsules (CT‐CPNCs) are mainly synthesized by in situ formation of crosslinked polymer shells on the surface of particulate cargoes, such as therapeutic proteins, siRNA/miRNA, liposomes, chitosans, metal‐organic frameworks (MOFs), and inorganic nanoparticles. CT‐CPNCs exhibit many advantages in biomedical applications, including 1) easy preparation and purification procedures, 2) high structural stability to inhibit undesired leakage of cargoes, and 3) high specific surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 176 publications
(174 reference statements)
0
6
0
Order By: Relevance
“…[100] More importantly, they can be easily modified with active ligands for targeting the cells or tissues. [101,102] In recent years, various types of polymers have been used for the fabrication of polymeric nanomaterials for biomedical applications. [103][104][105] For example, synthetic polymers are ideal candidates to design the MINPs with a tailor-made structure or a customized surface for molecular recognition.…”
Section: Polymeric Nanomaterialsmentioning
confidence: 99%
“…[100] More importantly, they can be easily modified with active ligands for targeting the cells or tissues. [101,102] In recent years, various types of polymers have been used for the fabrication of polymeric nanomaterials for biomedical applications. [103][104][105] For example, synthetic polymers are ideal candidates to design the MINPs with a tailor-made structure or a customized surface for molecular recognition.…”
Section: Polymeric Nanomaterialsmentioning
confidence: 99%
“…Other researchers ( Joseph et al, 2016 ) have reported a series of quaternary phosphine and quaternary ammonium groups modified columnar aromatic hydrocarbons for antibacterial applications. Wang et al ( Guo et al, 2021b ) constructed a new type of Guanidinium-modified pillar ( Zhao et al, 2021 ) arene (GP5), which can rapidly combine with the negative electrical components on the biofilm and the phospholipid components on the bacterial membrane through a salt bridge to dissolve the bacteria, to achieve antibacterial and anti-infection effects. Some nanomaterials can also play a role in inhibiting bacteria by trapping or blocking bacteria.…”
Section: Application Of Bioactive Nanomaterials In Biomedicinementioning
confidence: 99%
“…Biological detection, drug delivery, and disease diagnosis and prevention have become the research hotspots of nanoscience in the field of health care. Currently, ph-responsive, and enzyme-responsive nanomaterials, which are widely used in targeted drug delivery and controlled drug release ( Zhao et al, 2021 ), are materials that can change their physical and chemical properties (such as surface charge and chemical structure) in response to external stimuli such as light and heat, reactive oxygen species (ROS) levels, and pH changes. In recent years, bioactive nanomaterials have attracted extensive attention and attention.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, biological systems evolve compartmentalization strategies flexibly in regulating and maintaining metabolic reactions. 17,18 Channel proteins on the surface of compartments allow cargoes, including small molecules and ions, to transport across compartment membranes. 19 Most channel proteins regulate the transport of cargoes by undergoing a mechanical change (acting as "gates").…”
Section: ■ Introductionmentioning
confidence: 99%
“…In nature, biological systems evolve compartmentalization strategies flexibly in regulating and maintaining metabolic reactions. , Channel proteins on the surface of compartments allow cargoes, including small molecules and ions, to transport across compartment membranes . Most channel proteins regulate the transport of cargoes by undergoing a mechanical change (acting as “gates”). , For example, bacteria can reversibly open and close these “gates” to allow specific molecules to enter its interior, thereby mediating the flux of metabolites. , Similar metabolic processes have also been found in eukaryotic cells and organelles. Inspired by these natural systems, encapsulation of the enzymes into an artificial compartment with “gates” on its membrane would be an innovative strategy to achieve controllable enzyme activities.…”
Section: Introductionmentioning
confidence: 99%